Progesterone and Related Compounds in Hepatocellular Carcinoma: Basic and Clinical Aspects. (16th January 2013) - Yeh, Yao-Tsung; Chang, Chien-Wei; Wei, Ren-Jie; Wang, Shen-Nien
Abstract : Primary liver cancer is the fifth most common cancer worldwide and the third most common cause of cancer mortality. Hepatocellular carcinoma (HCC) accounts for 85% to 90% of primary liver cancers. Major risk factors for HCC include infection with HBV or HCV, alcoholic liver disease, and most probably nonalcoholic fatty liver disease. In general, men are two to four times more often associated with HCC than women. It can be suggested that sex hormones including progesterone may play some roles in HCC. Rather, very limited information discusses its potential involvement in HCC. This paper thus collects some recent studies of the potential involvement of progesterone and related compounds in HCC from basic and clinical aspects. In addition, two synthetic progestins, megestrol acetate (MA) and medroxyprogesterone acetate (MPA), will be discussed thoroughly. It is noted that progesterone can also serve as the precursor for androgens and estrogens produced by the gonadal and adrenal cortical tissues, while men have a higher incidence of HCC than women might be due to the stimulatory effects of androgen and the protective effects of estrogen. Eventually, this paper suggests a new insight on the associations of progesterone and related compounds with HCC development and treatment.